The Effect of Passive Dehydration on Phase Angle and Body Composition: A Bioelectrical Impedance Analysis - Aburto-Corona, Jorge A.; Calleja-Núñez, Juan J.; Moncada-Jiménez, José; de Paz, José Antonio (Nutrients, 2024)
Bioelectrical impedance analysis (BIA) is a method used to estimate body composition, and it relies mainly on the body’s water content. Insufficient body water can introduce bias to body composition scores. Purpose: To determine the effect of body weight loss elicited by passive dehydration on body composition scores, including phase angle (PhA). Methods: Twenty-five euhydrated apparently healthy and physically active men’s (age = 22.6 ± 3.3 yr.; body mass = 76.7 ± 15.9 kg; height = 172.0 ± 6.3 cm) body composition variables and PhA were measured before and after sitting quietly for 5 h in a controlled environment (26.6 ± 1.7 °C, 72 ± 4.9%RH). Results: It was found that five hours of passive dehydration caused a loss in body weight (Δ = 0.76 ± 0.34 kg, p < 0.05) and a decrease in body fat estimation (Δ = 0.90 ± 0.87 kg, p < 0.001). Additionally, an increase in ECW (Δ = 0.12 ± 0.30 L, p < 0.021) and PhA (Δ = 0.10 ± 0.15°, p < 0.005) was observed. Conclusion: Body weight loss due to passive dehydration decreased BIA-derived fat mass, and increased extracellular water and PhA in physically active and apparently healthy men. Nonetheless, these changes had a negligible effect on the accuracy of the equipment, rendering them clinically insignificant.